UPAYA KEPALA SEKOLAH DALAM MENINGKATKAN KREATIVITAS PEMBELAJARAN GURU DI ERA PANDEMIC COVID-19 PADA SMA NEGERI 7 LUWU UTARA - Aprilia Sumardi; Andi Nurochmah (Jurnal Administrasi, Kebijakan, dan Kepemimpinan Pendidikan (JAK2P), 2022)
The purpose of this research is to describe the efforts of the principal in improving teacher learning creativity in the pandemic era of covid-19 at SMA Negeri 7 Luwu Utara and to describe the form of teacher learning creativity in the pandemic era of covid-19 at SMA Negeri 7 Luwu Utara. The research approach used is qualitative approach with qualitative descriptive research type. The data source in this study is the Principal as a key informant, deputy principal and educator as a related supporting informant at SMA Negeri 7 Luwu Utara. The data collection techniques used in this study are observation, interview, and documentation. Data analysis uses data reduction analysis, data presentation, and conclusion drawing. Based on the results of the research showed that the efforts made by the principal in improving teacher learning creativity in the pandemic era covid-19 at SMA Negeri 7 Luwu Utara has been going well. This is demonstrated by the various efforts made by the principal through: Training, meetings, supervision, evaluation, and rewarding and punishment. The form of teacher learning creativity in the pandemic era covid-19 at SMA Negeri 7 Luwu Utara in the form of a video that is created to be more interesting so that students are more interested.